Cancer follow-up supported by patient-reported outcomes in patients undergoing intended curative complex surgery for advanced cancer - Sissel Ravn (SpringerOpen, 2021)
Abstract Background and aim Patient activation (PA) and Patient Involvement (PI) are considered elements in good survivorship. We aimed to evaluate the effect of a follow-up supported by electronic patient-reported outcomes (ePRO) on PA and PI. Method From February 2017 to January 2019, we conducted an explorative interventional study. We included 187 patients followed after intended curative complex surgery for advanced cancer at two different Departments at a University Hospital. Prior to each follow-up consultation, patients used the ePRO to screen themselves for clinical important symptoms, function and needs. The ePRO was graphically presented to the clinician during the follow-up, aiming to facilitate patient activation and involvement in each follow-up. PA was measured by the Patient Activation Measurement (PAM), while PI was measured by five indicator questions. PAM and PI data compared between (− ePRO) and interventional (+ ePRO) consultations. PAM data were analysed using a linear mixed effect regression model with intervention (yes/no) and time along with the interaction between them as categorical fixed effects. The analyses were further adjusted for time (days) since surgery. Results According to our data, ePRO supported consultations did not improve PA. The average mean difference in PAM score between + ePRO and − ePRO consultations were − 0.2 (95% confidence interval − 2.6; 2.2, p = 0.9). There was no statistically significant improvement in PAM scores over time in neither + ePRO nor − ePRO group (p = 0.5). Based on the five PI-indicator questions, the majority of all consultations were evaluated as “some, much or very much” involved in consultation; providing a wider scope of dialogue, encouraged patients to ask questions and share their experiences and concerns. Nevertheless, another few patients reported not to be involved at all in the consultations. Conclusion We did not demonstrate evidence for ePRO supported consultations to improve patient activation, and patient activation did not improve over time. Our results generate the hypotheses that factors related to ePRO supported consultation had the potential to support PI by offering a wider scope of dialogue, and encourage patients to ask questions and share their experiences and concerns during follow-up.